Pentacene disproportionation during sublimation for field-effect transistors - Roberson, Luke B.; Kowalik, Janusz; Tolbert, Laren M.; Kloc, Christian; Zeis, Roswitha; Chi, Xiaoliu; Fleming, Richard; Wilkins, Charles (Journal of the American Chemical Society, 2005)
At moderate temperatures in flowing gas, pentacene undergoes a disproportionation reaction to produce 6,13-dihydropentacene (DHP) and a series of polycondensed aromatic hydrocarbons, including the previously unknown peripentacene (PP). The process requires activation by heating to 320°C and is possibly catalyzed by impurities such as DHP, 6,13-pentacenequinone (PQ), Al, or Fe found in the starting materials. These impurities also result in a decrease in the intrinsic field-effect mobility (FEM) of pentacene crystals. Subsequent purifications remove such impurities, thus inhibiting the formation of the disproportionation products and increasing the FEM of pentacene (2.2 cm2/Vs). These results clarify the importance of purification of semiconductive materials for measurements of intrinsic mobility and optimal device performance. © 2005 American Chemical Society.
Created from Fastlane, Scopus look-up